Tindak Tutur Direktif dalam Ceramah Ustadz Hannan Attaki “Kalo Aku Dijahatin, Aku Harus Apa?” - Wahyuni, Tuti; Yuwantika, Diva; F, Fatmawati (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to explain the types and purposes of directive speech acts contained in Ustadz Hannan Attaki's lecture entitled